Skill-biased technical change and immiserizing growth - Alessio Moro; Silvio Tunis (Prague University of Economics and Business, Faculty of International Relations (FIR), 2024)
The combination of consumer preferences, technological changes, and different income elasticities among goods and services can generate inequalities among agents leading to winners and losers. Inspired by these mechanisms, we pose the following research question: "Can immiserizing growth (IG) emerge within a skill-biased technical change (SBTC) framework where all agents display the same preferences, and they only differ in their skill level and consequently in the wage rate earned in the market?". The methodology adopted is constructing a general equilibrium model within an SBTC framework characterised by heterogeneous agents in skills endowed by identical Stone-Geary preferences. The non-homothetic feature of these preferences enables agents to consume the same bundles in different proportions as income increases, providing consumption patterns more coherent with the real world. Exploring the sensitivity of the model, I identify, as key results, the underlying drivers capable of triggering IG situations: the non-homotheticity, the elasticity of substitution between labour inputs, and differential SBTC across sectors. No IG arises calibrating the model to the U.S. industries and labour data from the EU KLEMS dataset. Performing a series of counterfactual experiments reveals that a decrease (increase) in the annual growth factor for the high-skilled (low-skilled) population leads to IG situations.
Keywords: 330; Verelendungswachstum; Technischer Fortschritt; Qualifikation; Konsumentenpräferenzen; Einkommenselastizität der Nachfrage; Allgemeines Gleichgewicht; USA